Cooperative Secure Transmission in the Presence of Untrusted Relay - Dechuan Chen; Weiwei Yang; Jianwei Hu; Yueming Cai; Sen Zhu (International Journal of Distributed Sensor Networks)
Considering a nonregenerative untrusted relay network, we investigate three different secure transmission strategies, for example, noncooperative strategy, conventional amplify-and-forward (AF) strategy, and cooperative jamming (CJ) strategy. To thoroughly assess the secrecy performance achieved by the three strategies, we derive the closed-form expressions for the connection outage probability and secrecy outage probability regarding each strategy. Based on these expressions, the reliability and security tradeoff (RST) is examined to facilitate the design of the transmitting parameters. We then present the closed-form expression for the effective secrecy throughput (EST) and characterize the overall efficiency of these transmission strategies. Furthermore, we conduct the asymptotic analysis for the secrecy throughput, which enables us to determine the optimal transmission strategy under different scenarios. Our analytical and numerical results demonstrate that compared with the noncooperative and AF strategies, the CJ strategy possesses the best performance in terms of RST. Additionally, we also find that the EST performance of the AF strategy is nearly invariable when the quality of the second hop changes.